Co-ingestion of amatoxins and isoxazoles-containing mushrooms and successful treatment: A case report. (1st September 2015) - Garcia, Juliana; Costa, Vera M.; Costa, Ana Elisa; Andrade, Sérgio; Carneiro, Ana Cristina; Conceição, Filipe; Paiva, José Artur; de Pinho, Paula Guedes; Baptista, Paula; de Lourdes Bastos, Maria; Carvalho, Félix
Abstract: Mushroom poisonings occur when ingestion of wild mushrooms containing toxins takes place, placing the consumers at life-threatening risk. In the present case report, an unusual multiple poisoning with isoxazoles- and amatoxins-containing mushrooms in a context of altered mental state and poorly controlled hypertension is presented. A 68-year-old female was presented to São João hospital (Portugal) with complaints of extreme dizziness, hallucinations, vertigo and imbalance, 3 h after consuming a stew of wild mushrooms. The first observations revealed altered mental state and elevated blood pressure. The examination of cooked mushroom fragments allowed a preliminary identification of Amanita pantherina . Gas chromatography–mass spectrometry (GC–MS) showed the presence of muscimol in urine. Moreover, through high-performance liquid chromatography-ultraviolet detection (HPLC-UV) analysis of the gastric juice, the presence of α-amanitin was found, showing that amatoxins-containing mushrooms were also included in the stew. After 4 days of supportive treatment, activated charcoal, silybin and N-acetylcysteine, the patient recovered being discharged 10 days post-ingestion with no organ complications. The prompt and appropriate therapy protocol for life-threatening amatoxins toxicity probably saved the patient's life as oral absorption was decreased and also supportive care was immediately started. Highlights: An intoxication with mushrooms with psychotropic symptoms is reported. In spite of the symptoms, prompt therapy for the amatoxins poisoning was immediately applied. Poisoning by Amanita pantherina and Amanita phalloides was confirmed after treatment initiation. The prompt therapy for Amanita phalloides poisoning possibly saved the patient's life. The protocol for Amanita phalloides poisoning is endorsed in all cases of mushrooms' intoxications.